Methods in historical corpus pragmatics: epistemic stance in early modern English - Landert, Daniela (Cambridge University Press, 2024)
Based on an extensive corpus-based study, this revealing book explores how epistemic stance is expressed in the early modern period, and in doing so, presents new methodologies for using corpora to investigate issues in historical pragmatics. It provides a new, corpus-driven method for the analysis of pragmatic functions that rely on context-dependent interpretations. By retrieving passages that include a high-density of the pragmatic function under investigation, the subsequent analysis can reveal previously neglected forms and context-dependent factors. It includes four empirical studies that apply the method to the analysis of epistemic stance in four Early Modern English corpora, the result of which emphasise the importance of context for the expression of stance. It also includes an appendix with inventories of Early Modern English stance expressions, offering starting points for further research studies. It is essential reading for researchers and students in historical pragmatics and corpus pragmatics.
Title from publisher's bibliographic system (viewed on 22 Feb 2024)
Keywords: Geschichte 1410-1760; Epistemologische Überzeugung; Korpus; Frühneuenglisch; Historische Pragmatik